Efficient Bioreduction of Sulfate from Industrial Wastewater Effluents Using Enterobacter cloacae emr69 - Abduallah, Eman R.; Saad, Eman M.; Aboseidah, Akram A.; Rasmey, Abdel-Hamied M. (Journal of Advanced Veterinary Research, 2023)
This study aimed to isolate and characterize sulfur reducing bacteria from industrial wastewater and soil to remove sulfate. A total of 14 sulfate reducing bacterial (SRB) isolates were recovered from industrial wastewater and contaminated soil. Interestingly, bacterial isolate emr69 was selected as the highest sulfate reducer. Correspondingly, emr69 was characterized phenotypically and identified genotypically based on 16S rRNA gene sequencing as Enterobacter cloacae and deposited in Gen Bank database under accession number OR472728. The maximum sulfate reduction by E. cloacae emr69 against 2000 ppm (SO4-2) was 95% which obtained by adjusting the medium at pH 6 and growing the bacterium at 37Â°C under anaerobic conditions. The study suggests using of E. cloacae mr69 as a promising SRB for bioreduction of sulfate in industrial wastewater treatment.